Pembelajaran Pendidikan Agama Islam Berbasis Karakter di SMP Alam Mahira Kota Bengkulu - Dino Kurniawan; Hery Noer Aly; Qolbi Khoiri (UIN Fatmawati Sukarno Bengkulu, 2023)
Character formation is a very basic highlight of the educational process because there are various cases of moral decadence that occur in students, besides that PAI learning in formal schools is felt to be less than optimal in internalizing religious values, while in natural schools the concept is following the formation of a religious character. The formulation of the problem of this research is 1. How to Plan Natural School-Based PAI Learning to Form Religious Character at Alam Mahira Middle School Bengkulu, 2. How to Implement Natural School-Based Islamic Religious Education Learning to Form Religious Character at Alam Mahira Middle School Bengkulu? 3. How is Learning Evaluation Natural School- Based PAI to Form Religious Character at Alam Mahira Middle School Bengkulu? This study used qualitative research methods. Data sources for school principals, PAI teachers, and students. Data collection techniques that researchers use are interviews, observation, and documentation. Qualitative data were analyzed using data reduction, data presentation, and data verification. The results of this study are (1). The character-based PAI learning plan in the Alam Mahira Middle School consists of: a). The aim is for the participants to love nature and strengthen monotheism in Allah. b). The special curriculum is Attitude of Life. c). Competence consists of good faith, reading the Qur'an properly and correctly, discipline in performing daily worship, and protecting the environment. (2). The implementation of PAI learning consists of a). habituation approach, b). Lecture method, discussion, role play, and story method, c). Learning resources are Al- Qur'an and Hadith, PAI printed books, and nature. d). Learning media: Projectors, laptops, learning videos, CDs/tapes, and nature. (3). Evaluation, the teacher assesses through tests and reports on natural school narratives and national education reports.